Hyperactivity and Inattention in Young Patients Born With an Atrial Septal or Ventricular Septal Defect - Sara Hirani Lau-Jensen; Benjamin Asschenfeldt; Benjamin Asschenfeldt; Lars Evald; Vibeke E. Hjortdal; Vibeke E. Hjortdal (Frontiers Media S.A., 2021)
Background: Patients with congenital heart defects have a well-established risk of neuropsychiatric comorbidities. Inattention and hyperactivity are three to four times more frequent in children with complex congenital heart defects. We have previously shown a higher burden of overall attention deficit/hyperactivity disorder (ADHD) symptoms in adults with simple congenital heart defects as well. However, it is unknown whether the higher burden of ADHD symptoms is mainly driven by hyperactivity, inattention, or both.Methods: The participants [simple congenital heart defect = 80 (26.6 years old), controls = 36 (25.3 years old)] and a close relative for each (n = 107) responded to the long version of the Conners' Adults ADHD Rating Scales questionnaire. Our primary and secondary outcomes are mean T-scores in the ADHD scores and symptom sub-scores.Results: Patients with simple congenital heart defects reported a higher mean T-score at all three DSM-IV ADHD scores (ADHD-combined: 52.8 vs. 44.9, p = 0.007, ADHD-inattention: 55.5 vs. 46.4, p = 0.002, and ADHD-hyperactivity: 49.4 vs. 44.0, p = 0.03) and in all four ADHD symptom sub-scores (inattention/memory problems: 50.3 vs. 44.2, p = 0.001, hyperactivity/restlessness: 49.7 vs. 45.9, p = 0.03, impulsivity/emotional lability: 50.0 vs. 41.3, p = 0.001, and self-esteem problems: 53.8 vs. 46.3, p = 0.003). The results were maintained after the removal of outliers (incongruent responses), albeit the hyperactivity/restlessness ADHD symptom sub-score lost significance. Self- and informant ratings differed significantly on the ADHD-inattention score for the congenital heart defect group, where informants rated the ADHD-inattention scores better than the congenital heart defect patients rated themselves.Conclusions: Patients with a simple congenital heart defect have a higher symptom burden across all ADHD scores and all symptom sub-scores. The higher burden of ADHD is driven by both inattention and hyperactivity symptoms, though the inattention symptoms seem more prominent. Close relatives were less aware of the inattention symptoms than the congenital heart defect patients themselves. Routine screening for ADHD symptoms may be warranted to facilitate adequate help and guidance as these symptoms are easily overlooked.Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT03871881.